Uganda GCF FREL Analysis: R-Project - Steward, Peter Richard; Engdaw, Mastawesha Misganaw; Ghosh, Aniruddha; Rosenstock, Todd Stuart (2023)
This R-project was used to estimate emissions from forest loss in Uganda for a GCF proposal, it is based on data from the Uganda FREL.